2017
DOI: 10.1177/0741932516678823
|View full text |Cite
|
Sign up to set email alerts
|

Model Drawing Strategy for Fraction Word Problem Solving of Fourth-Grade Students With Learning Disabilities

Abstract: This study used a multiple probe across participants design to examine the effects of a model drawing strategy (MDS) intervention package on fraction comparing and ordering word problem–solving performance of three Grade 4 students. MDS is a form of cognitive strategy instruction for teaching word problem solving that includes explicit instruction in drawing bar diagrams to represent problem components. Results suggest the intervention package was effective for improving the fraction word problem solving of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
36
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 39 publications
3
36
0
2
Order By: Relevance
“…All studies clearly defined and described the fraction performance measure(s) of each dependent variable. Five studies utilized researcher created measures (Agrawal, ; Everett et al, ; Reneau, ; Sharp & Shih Dennis, ; Westenskow & Moyer‐Packenham, ), five used standardized measures (Fuchs et al, , ; Fuchs, Malone, et al, ; Fuchs, Schumacher, et al, ; Turner, ), and two incorporated both types of measures (Hunt, ; Watt & Therrien, ). For each single‐subject design study, inter‐rater reliability of 80% or higher was reported.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All studies clearly defined and described the fraction performance measure(s) of each dependent variable. Five studies utilized researcher created measures (Agrawal, ; Everett et al, ; Reneau, ; Sharp & Shih Dennis, ; Westenskow & Moyer‐Packenham, ), five used standardized measures (Fuchs et al, , ; Fuchs, Malone, et al, ; Fuchs, Schumacher, et al, ; Turner, ), and two incorporated both types of measures (Hunt, ; Watt & Therrien, ). For each single‐subject design study, inter‐rater reliability of 80% or higher was reported.…”
Section: Resultsmentioning
confidence: 99%
“…All studies utilized the primary researcher or research team member (i.e., graduate students) as the instructor for intervention sessions. Five studies included instructors with prior education experience (Agrawal, ; Reneau, ; Sharp & Shih Dennis, ; Watt & Therrien, ; Westenskow & Moyer‐Packenham, ), six studies utilized graduate students (Everett et al, ; Fuchs et al, , ; Fuchs, Malone et al, ; Fuchs, Schumacher et al, ; Hunt, ), and one study did not provide interventionist background information (Turner, ). All but two studies (Everett et al, ; Turner, ) described the training or qualifications necessary to implement the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations